PENGARUH PROGRAM GREEN HOTEL TERHADAP KEPUTUSAN MENGINAP TAMU DI THE ROYALE KRAKATAU HOTEL CILEGON BANTEN - Abdullah, Taufik; Pebriyanti, Kiki (Universitas Pendidikan Indonesia, 2016)
Tourism is an industry that is considered promising is helping the economy and prosperity of a country. There are many things that support tourism, a sector that is important in the means of accomodation. There are several accomodation facilities such as travel agent, hotels and restaurants. Hotel is one property which is important for travelers to stay. Nowdays, competition among hotel industries is very high. There are a lot of hotel that have proven strategies in marketing their hotels. The Royale Krakatau is one of hotels which located in Cilegon, Banten area. The royale krakatau hotel is a hotel that has been existing for a long time, was originally only in the form of a guest house, and now it has become a 4 star hotel. Although the royale krakatau hotel has been existing for a long time, the available facilities are not less complete than other hotels. The royale krakatau hotel does various methods to compete than other hotels in order to enhance guest staying decision. One of them is by using green hotel program. Green hotel is a strategy in which the implementation of thie program considers several things such as clean, green, and well-organized environment concept. Green hotel is x variable in this study which consist of recyled materials, recyclable, Low-polluting and energy saving. The depend variable in this study is a decision to stay which consist of product selection, brand selection, visit time, total purchases and payment method. This reserch is descriptive verification, and sampling method is obtained from 100 respondent of FIT guest who stay at The Royale Krakatau Hotel Cilegon. The used technique of data analysis and hypothesis testing is multiple regression analysis. The result showed that the positive influances between hotel program an decison to stay at The Royale Krakatau Hotel Cilegon.